Effect of Low-melting-point Curing Agent on Property of Epoxy Resin - REN Zhi-dong; LIANG Chen-xi; HAO Si-jia; XING Yue; TIAN Jun-peng; DAI Sheng-long; YANG Cheng (Cailiao gongcheng, 2018)

(untitled)
Effect of low-melting-point curing agent (MOEA) on property of epoxy resin was studied. The properties of epoxy resin (MOEA40) with MOEA as the curing agent were characterized and compared with the epoxy resin (DDM30) with 4, 4'-diaminodiphenyl methane (DDM) as the curing agent. The viscosity-temperature property, curing behavior, mechanical properties and thermal properties were characterized by rotational rheometer, differential scanning calorimetry (DSC), universal material testing machine, dynamic thermomechanical analyzer (DMA) and thermal gravimetric analyzer (TGA), respectively. The results show that MOEA40 has better viscosity-temperature property than that of DDM30. MOEA shows low viscosity (0.2-3.5Pa·s) in the temperature range of 60-140℃. MOEA40 and DDM30 are cured with the same curing progressing. Cured MOEA40 shows outstanding mechanical properties with bending strength about 147MPa and tensile strength about 89 MPa, which are 9.7% and 11.2% higher than that of cured DDM30 (bending strength 134MPa, tensile strength 80MPa). In addition, cured MOEA40 shows higher glass transition temperature (168℃) and higher thermal stability with 5% mass loss temperature about 367℃ in nitrogen atmosphere.